Seni Rupa Sebagai Stimulasi Visual Dalam Pembelajaran Pai Untuk Anak Usia Sekolah Dasar/MI - Saidah, Nur (Universitas Alma Ata, 2013)
According to psychological development of young child at elementary school, at least there are two main reasons of visual stimulative utilization using fine art work in teaching-learning process. The first, visual stimulation is more interesting thing to enrich child motivation in learning because the students will enjoy the process, the materials can be explained easily, teaching method will be varied and the students will involve themselves in teaching-learning process, not only listening the lesson from teacher but also observing, searching or demonstrating massage of the illustration. The second, visual stimulation is appropriate to psychological development of the children in the elementary school because this media explain the abstract concept become the concrete one and simplify the complexity of the lesson. It is very important to PAI learning process which much of it’s materials consist of the abstract concept. More over using visual stimulation will give the teacher positivity to make Joyful Learning which students may learn not under pressure and the learning process of PAI will be productive, full of creativities, activities, effectiveness and joyfulness. Keywords: Visual stimulation, psikologis development.